PENGARUH BUDAYA ORGANISASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT. NISSIN KOGYO BATAM - JUNITA SARI; REALIZE . (LP2MTBM MAKARIOZ, 2020)
The development and competition of the global industry at this time in Indonesia is getting tougher so that, in thesecircumstances management in the company must be managed properly. Therefore, human resources are very much neededas a driving force in the development of organizations or companies, such as being able to create quality human resources,capable and skilled in order to compete in the global era. To gain a competitive advantage, companies need to analyze theirresources to identify their weaknesses and strengths in order to build capability so employees are expected to work well andprofessionally from a total of 256 populations, using a sample of saturated respondents taken using incidental samplingmethod that collects data using primary and secondary sources by distributing questionnaires using a Likert scale. whichmeasures 32 statements. This analysis uses multiple linear regression test in which the data is processed by SPSS 22. Theresults of the f test which shows the organizational culture and motivation simultaneously have a significant influence onemployee performance at PT. Nissin kogyo Batam. Partial t test results, it is known that the organizational culture variablepartially has a positive and significant effect on employee performance by including a significance amount of 0,000 <0.005.Motivation variable partially has a positive and significant effect on employee performance by including a number ofsignificance values of 0.003 <0.005.